Teacher evaluation to enhance professional practice - Danielson, Charlotte; McGreal, Thomas L. (Alexandria, VA : Association for Supervision and Curriculum Development ; Princeton, NJ : Educational Testing Service, 2000)
Identifies some of the problems with many teacher evaluation systems, presents a rationale for teacher evaluation, and describes a structural framework for designing an effective evaluation system for beginning and tenured teachers.
"ASCD product no. 100219"--T.p. verso.
Includes bibliographical references (p. 152) and index.
Professional
Professional
Keywords: Teachers -- Rating of -- United States; Teaching -- United States -- Evaluation; Teachers -- United States; Teaching -- United States -- Evaluation